An MOT-TDIE Solver for Analyzing Transient Fields on Graphene-Based Devices - Shi, Yifei; Li, Ping; Uysal, Ismail E.; Ulku, H. Arda; Bagci, Hakan (IEEE, 2016)
A marching on-in-time (MOT) scheme for analyzing transient electromagnetic wave interactions on devices consisting of graphene sheets and dielectric substrates is proposed. The MOT scheme discretizes time domain resistive boundary condition (TD-RBC) and Poggio-Miller-Chang-Harrington-Wu-Tsai (TD-PMCHWT) integral equation, which are enforced on the surfaces of the graphene and dielectric substrate, respectively. The expressions of the time domain resistivity and conductivity of the graphene sheet are obtained analytically from the intra-band contribution formulated in frequency domain. Numerical results, which demonstrate the applicability of the proposed scheme, are presented.
IEEE-Antennas-and-Propagation-Society International Symposium -- JUN 26-JUL 01, 2016 -- Fajardo, PR
Keywords: Time domain integral equation; graphene; resistive boundary condition; numerical analysis